Comparing personal insight gains due to consideration of a recent dream and consideration of a recent event using the Ullman and Schredl dream group methods - Edwards, Christopher L.; Malinowski, Josie E.; McGee, Shauna L.; Bennett, Paul D.; Ruby, Perrine M.; Blagrove, Mark T. (Frontiers in Psychology, 2015)
There have been reports and claims in the psychotherapeutic literature that the consideration of recent dreams can result in personal realizations and insight. There is theoretical support for these claims from work on Rapid Eye Movement sleep having a function of the consolidation of emotional memories and the creative formation of connections between new and older memories. To investigate these claims, 11 participants (10 females, 1 male) reported and considered a recent home dream in a dream discussion group that following the ‘Appreciating dreams’ method of Montague Ullman. The group ran 11 times, each participant attending and participating once. A further nine participants (7 females, 2 males) reported and considered a recent home dream in a group that followed the ‘Listening to the dreamer’ method of Michael Schredl. The two studies each had a control condition where the participant also reported a recent event, the consideration of which followed the same technique as was followed for the dream report. Outcomes of the discussions were assessed by the participants on the Gains from Dream Interpretation scale, and on its counterpart, the Gains from Event Interpretation scale. High ratings on the GDI experiential-insight subscale were reported for both methods, when applied to dreams, and for the Ullman method exploration-insight ratings for the dream condition were significantly higher than for the control event condition. In the Ullman method, self-assessment of personal insight due to consideration of dream content was also significantly higher than for the event consideration condition. The findings support the view that benefits can be obtained from the consideration of dream content, in terms of identifying the waking life sources of dream content, and because personal insight may also occur. To investigate the mechanisms for the findings, the studies should be repeated with REM and NREM dream reports, hypothesizing greater insight from the former.